Effects of Vegetative Cool‐Season Grasses on Forage Removal by Dairy Heifers. (1st July 2017) - Billman, Eric D.; Goff, Ben M.; Baldwin, Brian S.; Prince, Kelly; Phillips, Tim D.
Abstract : Core Ideas: Grazing of vegetative swards results in forage removal trends contradictory to established paradigms. Neutral detergent fiber, and water soluble carbohydrates did not impact forage removal in ways established by studies done on grass with varying maturity. Conclude that species differences rather than cultivars drive forage removal in dairy cattle. Identification of forage grasses that are more readily consumed than others during grazing is vital to determining traits that can be used by plant breeders to increase animal intake and digestibility. Producers can benefit from the identification of what species and cultivars are more readily consumed; thus increasing animal production. The objectives were to: (i) determine forage removal by dairy cattle of several species and cultivars of cool‐season forage grasses: orchardgrass ( Dactylis glomerata L.; eight cultivars), tall fescue [ Schedonorus arundinaceus (Schreb.) Dumort; five cultivars], perennial ryegrass ( Lolium perenne L.; five cultivars), and festulolium [ × Festulolium braunii (K. Richt.) A. Camus; six cultivars]; and (ii) determine if forage nutritive value is correlated with forage removal by animals on vegetative pasture. Forage removal for species varied among seasons; orchardgrass and festulolium were consumed more in spring, while orchardgrass and tall fescue were consumed more in the summer, and species did not affect removal in the fall. Forage removal varied among cultivars. However, when comparing forage removal against neutral detergent fiber (NDF), acid detergent fiber (ADF), crude protein (CP), in vitro true digestibility (IVTD), water soluble carbohydrates (WSC), pre‐grazing herbage mass, sward height, and dry matter concentration, correlations did not adhere to the paradigm of fiber fraction being negatively correlated and nutrient components being positively correlated to forage removal. This indicated that other factors impact forage removal when animals graze completely vegetative swards.